LOOKING AT THE FUTURE FOR COMPREHENSIVE CARE FOR THE ELDERLY - อัครางกูร ปภาภัทร (RMUTT Global Business and Economics Review, 2019)
Currently, the elderly account for more than 10% of the total population; however, the elderly healthcare facilities available are incompatible with the increased number. This article focuses on a comprehensive healthcare program for the elderly: physical, mental, economic, social and spiritual. The spiritual aspect plays a more important role than the others because this will assure the elderly of their self-worthiness and confidence that they can take care of themselves. This program will prepare the elderly for the aging society.This article would like to point out that at present the elderly’s needs have not been met especially those who can access the existing services for the elderly without financial support from the government but such services are not comprehensive. As a result, a comprehensive healthcare center for the elderly that can be under the supervision of either the government or the public sector should be established to improve their quality of life.